Surface properties and in vitro biocompability of a track membrane based on polyethylene terephthalate after exposure to low-temperature atmospheric plasma and ionizing γ -radionuclide 60Сo - E. О. Filippova (Bûlleten' Sibirskoj Mediciny, 2018)
Aim. This research studies the effect of a low-temperature atmospheric plasma and the subsequent γ-ray sterilization on topography and properties of track membranes (TM) based on polyethylene terephthalate (PET).Materials and methods. TM were obtained by irradiating a PET film with a 40Ar+8 ion beam and then by chemical etching in an aqueous solution of 1.5N NaOH. Modification of the membrane surface was carried out by exposure to an atmospheric low-temperature plasma. The gamma radiation of the radionuclide 60Со with the dosages of 1kGy (SI) and 10 kGy (SI) was used to sterilize the membranes. In vitro studies of the TM biocompatibility were performed by using a culture of prenatal stromal cells isolated from a lung of an 11-week human embryo and maintained ex vivo.Results. It has been established that the treatment of the membranes with the low-temperature atmospheric plasma leads to an increase in the roughness and hydrophilization of the TM surface. The change in the physical-chemical state of the TM surface as a result of the exposure of cold plasma and subsequent sterilization had practically no effect on the morphofunctional state of the culture of human prenatal stromal cells. In vitro tests on the TM cellular-molecular biocompability with a short-term culture of in vitro fibroblast-like cells have made it possible to indicate their relative bioinerticity with respect to human stromal cells. The conclusion is made about the relative bioinerticity of TM and the proposed regimes for their sterilization with respect to the culture of human stromal cells, the prospects for further research in applying the material to the areas of surgical practice (cardiology, ophthalmology).